(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2024)
Structures erected on soft soil often face challenges related to uncontrollable settlement and critical bearing capacity. The footing of numerous structures is prone to failure and collapse when situated on weak soil. In geotechnical engineering, enhancing the bearing capacity of a shallow footing is imperative. Ground reinforcement techniques are employed to improve the properties of weak soils, particularly addressing issues of compressibility and bearing capacity. One method for achieving this improvement is the use of woven geotextile reinforcement, as soil is proficient in compression but lacks tensile strength. By incorporating woven geotextile, the tensile potential of the soil is increased, consequently enhancing its load-bearing capacity. This paper reviews potential benefits of woven geotextile’s (WG) in improvement the bearing capacity of square footing rest on clay soil. The model footing load tests were conducted on woven geotextile layers were added at varying distances. The findings demonstrated that, in comparison to unreinforced soil, the use of a woven geotextile system for reinforcement greatly increased bearing capacity and reduce settlement beneath the square foundation. Compared with unreinforced soil the ultimate bearing capacity increased about 1.91 times when reinforced with three layers of woven geotextile. Furthermore, the study employs advanced modeling techniques, utilizing the Plaxis-3D software program, to rigorously analyze the experimental results obtained from model footing tests. The results of these tests provide valuable insights into the effectiveness of the woven geotextile, contributing to a better understanding of their influence on soil stability and foundation support.